2020
DOI: 10.1177/1403494820914802
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and time trends of overweight, obesity and severe obesity in 447,925 Swedish adults, 1995–2017

Abstract: Aims: The purpose of this research was to describe the current prevalence and historic trends in overweight, obesity and severe obesity in Sweden. Methods: Data on BMI, age, gender, education and geographic region were obtained in n=447,925 Swedish adults through a nationwide screening test (1995–2017). To account for sampling variations, we quantified prevalence estimates and time trends using standardized values (direct method) to all 18–74-year-old Swedes, using nationwide databases. Rates of overweight (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 31 publications
8
47
0
1
Order By: Relevance
“…26 The prevalence of overweight in children and their parents has shown to be higher in rural compared with urban areas. 12,39 Moraeus et al have suggested that targeting rural areas might be an effective approach to reach children with the greatest needs. 39 Two-thirds of the children in this study reduced their degree of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The prevalence of overweight in children and their parents has shown to be higher in rural compared with urban areas. 12,39 Moraeus et al have suggested that targeting rural areas might be an effective approach to reach children with the greatest needs. 39 Two-thirds of the children in this study reduced their degree of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The previous rapid increase in the prevalence of childhood obesity in Sweden may have haltered 10 . The prevalence of childhood and adult obesity is higher in the less densely populated northern parts of Sweden than in other parts of the country 11,12 . A decline in childhood overweight and obesity has been noticed also in rural areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong association between socioeconomic status and body weight, with an increasing risk of becoming overweight or obese in people with lower socioeconomic status 15 18 . In addition, individuals living in rural areas are more likely to be overweight or obese, even though this risk is attenuated when accounting for educational level 19 .…”
Section: Introductionmentioning
confidence: 99%
“…1), with a flattening and marked shift to the right, especially for waist circumference. Line graphs of the prevalence rates at the different survey time points paint a similarly bleak picture: a clear and drastic increase, with no discernible signs of a slowdown, mirroring the developments seen in the US and elsewhere [1,2] While obesity aetiology is multifactorial, including many aspects that are still not well understood, there are also likely to be underlying factors that are specific to China, such as previous famines and social policies. But the main overall driver is likely to be China's exceptionally rapid economic growth [5].…”
mentioning
confidence: 99%